Teams under pressure in the emergency department: an interview study. - Flowerdew, L; Brown, R; Russ, S; Vincent, C; Woloshynowych, M (2012)
OBJECTIVE: To identify key stressors for emergency department (ED) staff, investigate positive and negative behaviours associated with working under pressure and consider interventions that may improve how the ED team functions. METHODS: This was a qualitative study involving semistructured interviews. Data were collected from staff working in the ED of a London teaching hospital. A purposive sampling method was employed to recruit staff from a variety of grades and included both doctors and nurses. RESULTS: 22 staff members took part in the study. The most frequently mentioned stressors included the '4-hour' target, excess workload, staff shortages and lack of teamwork, both within the ED and with inpatient staff. Leadership and teamwork were found to be mediating factors between objective stress (eg, workload and staffing) and the subjective experience. Participants described the impact of high pressure on communication practices, departmental overview and the management of staff and patients. The study also revealed high levels of misunderstanding between senior and junior staff. Suggested interventions related to leadership and teamwork training, advertising staff breaks, efforts to help staff remain calm under pressure and addressing team motivation. CONCLUSIONS: This study highlights the variety of stressors that ED staff are subject to and considers a number of cost-efficient interventions. Medical education needs to expand to include training in leadership and other 'non-technical' skills in addition to traditional clinical skills.